Delayed Diagnosis of McCune–Albright Syndrome - Bereket Fantahun; Seblewongel Desta (Case Reports in Genetics)
Background. McCune–Albright syndrome (MAS) is a rare heterogeneous genetic disorder that is characterized by a triad of polyostotic fibrous dysplasia (FD), café au lait spots (CAL), and multiple hyperfunctional endocrinopathies. In general, it is diagnosed clinically. From the triads, two of the findings are enough to make the diagnosis, but genetic testing can be done if it is available. Case Presentation. We report a female child who was symptomatic since the neonatal period with skin hyperpigmentation, breast enlargement, and vaginal bleeding. She was diagnosed with MAS at the age of five years. She had pathological fractures at multiple sites and had raised thyroid hormones since the age of 3½ years. The child developed severe morbidity as the result of delayed diagnosis and currently became wheelchair dependent. Conclusion. Thorough patient evaluation and appropriate interpretation of findings are crucial steps for timely diagnosis of MAS and better patient care outcomes.